UNDERSTANDING POSTMODERNISM: NORTHERN BLOCKS OF PODIL (City: History, Culture, Society, 2019)
Reevaluation of Soviet heritage is a contested topic nowadays. At this moment debates are happening about the attempts to conserve the projects of High Modernism in the USSR of the 1970s and 1980s or even to designate them as heritage. In this article, however, the author attempts to reveal another dimension: postmodern architecture within the life span of the Soviet Union. The case discussed in the article is a housing estate “4blocks” located on the edge of the industrial zone in the Podil district in Kyiv, Ukraine.Podil area was spared from being rebuilt according to the modernist planning proposal in 1968. Afterwards, the district became a testing ground for experimental projects, part and parcel of which is the “4blocks” housing. One can perceive this project being a watershed between different periods of late modernism and postmodernism because of the specific architectural approach and the influence this project exerted on the following architectural production. In the article, the unique conditions which allowed the team of architects to work with unprecedented freedom are discussed. In what way did architects reflect on and use international influences in their projects? How did they work with the local peculiarities of landscape, materials, built environment and archaeology?The article also touches upon the topic of the change in approaches toward the historic urban areas in the late USSR. To highlight the parallels between local and international contexts and reflect on the resulting project the author uses the then-contemporary poststructuralist philosophy. Similarities of the concepts put forward by the philosophy in its critique of architectural Modernism and those used by the authors in “4blocks” is striking. One can conclude that Ukrainian Soviet architecture evolved into a variety of different styles in the mid-1980-s, and this project can be considered a vivid example of one of such styles, so-called postmodernism.
Keywords: Podil; architecture of the USSR; modernism; postmodernism; heritage; quality criteria; built environment